STAT6 Reliably Distinguishes Solitary Fibrous Tumors from Myofibromas - Smith, Molly Housley (Head Neck Pathol, 2017)
Solitary fibrous tumors (SFT) and myofibromas (MF) historically have belonged to the same morphologic spectrum and have been lumped together under the nonspecific umbrella term, “hemangiopericytoma” along with other pericytic/myoid tumors. While current evidence shows clear distinction between the two entities, they frequently remain in the same histopathologic differential diagnosis. This diagnostic dilemma especially is common for smaller incisional biopsies from the oral cavity. STAT6 immunohistochemistry (IHC) recently was established as a reliable method to detect solitary fibrous tumor; however, the literature is sparse regarding STAT6 reactivity in MFs. The authors report ten new cases of oral solitary fibrous tumor, discuss histopathologic similarities and differences between the two tumors, and list respective STAT6 IHC expressivity. After IRB approval, 10 cases diagnosed as SFT and 24 cases of MF were collected from the University of Florida Oral and Maxillofacial Pathology Biopsy Service between the years 1994 and 2016. The original hematoxylin and eosin slides and related IHC were reviewed. IHC with STAT6 antibody was performed on all 34 samples, and the findings were analyzed. All cases were from the oral cavity or perioral regions. 10/10 SFTs expressed STAT6 nuclear reactivity, while no cases of MF showed nuclear expression of STAT6. STAT6 is a dependable marker to differentiate SFTs from MFs.